Dihydromyricetin Inhibits M1 Macrophage Polarization in Atherosclerosis by Modulating miR-9-Mediated SIRT1/NF-κB Signaling Pathway - Zhousheng Yang; Tianyu Li; Chunyan Wang; Mingyu Meng; Shenglan Tan; Lei Chen (Mediators of Inflammation)
Dihydromyricetin (DMY), a natural flavonoid compound extracted from the stems and leaves of Ampelopsis grossedentata, has been found as a potential therapeutic chemical for treating atherosclerosis. This study explores the underlying mechanism of DMY repressing M1 macrophage polarization in atherosclerosis. We showed that DMY treatment markedly decreased M1 macrophage markers (e.g., Tnf-α and IL-1β) and p65-positive macrophage numbers in the vessel wall of Apoe-deficient (Apoe–/–) mice. Overexpression of miR-9 or knockdown of SIRT1 in macrophages reversed the effect of DMY on M1 macrophage polarization. The data we presented in the study indicate that the miR-9-mediated SIRT1/NF-κB pathway plays a pivotal role in M1 macrophage polarization and is one of the molecular mechanisms underlying the anti-atherosclerosis effects of DMY. We provide new solid evidence that DMY may be explored as a potential therapeutic adjuvant for treating atherosclerosis.